2022
DOI: 10.3389/fonc.2021.810249
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Intervention With High-Oleocanthal and Oleacein Olive Oil in Patients With Early-Stage Chronic Lymphocytic Leukemia: A Pilot Randomized Trial

Abstract: AimOleocanthal and oleacein (OC/OL) have important in vitro and in vivo antitumor properties; however, there is no data about their anticancer activity in humans. The aim of this pilot study was to test if patients at early stage of chronic lymphocytic leukemia (CLL) could adhere to and tolerate an intervention with high OC/OL extra virgin olive oil (EVOO) and if this intervention could lead to any changes in markers related to the disease.MethodsA pilot dietary intervention (DI) was made in patients with CLL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Finally, Rojas Gil et al’s pilot study (NCT04215367) described the effects of the two main components of extra virgin olive oil (EVOO) on patients suffering from chronic lymphocytic leukemia (CLL) [ 106 ]. EVOO is a major component of the MedDiet, and it is accountable for the beneficial effect exerted by this dietary pattern [ 17 ].…”
Section: Evidence From the Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Rojas Gil et al’s pilot study (NCT04215367) described the effects of the two main components of extra virgin olive oil (EVOO) on patients suffering from chronic lymphocytic leukemia (CLL) [ 106 ]. EVOO is a major component of the MedDiet, and it is accountable for the beneficial effect exerted by this dietary pattern [ 17 ].…”
Section: Evidence From the Clinical Trialsmentioning
confidence: 99%
“…Overall, these data posed the first evidence of the beneficial effect of high OC/OL EVOO on the improvement of CLL by exerting a proapoptotic influence on cancer cells. A multi-center larger trial must be carried out to confirm this preliminary evidence [ 106 ].…”
Section: Evidence From the Clinical Trialsmentioning
confidence: 99%
“…Results suggested an acute anti-platelet effects in healthy men[12]. Another pilot study tested an intervention with high oleocanthal and oleacein EVOO in 26 patients at early stage of chronic lymphocytic leukemia[13]. Authors concluded that it could be a promising dietary approach for the improvement of this disease[13].…”
Section: Introductionmentioning
confidence: 99%
“…In a small, prospective trial including 30 patients with advanced small cell lung cancer randomized to a personalized the MedDiet vs. a control diet, the MedDiet was associated with lower levels of inflammatory markers after 3 months, which suggests that it may positively influence cancer prognosis [ 14 ]. Another small, randomized trial concluded that a nutritional intervention based on extra-virgin olive oil rich in two polyphenols showing in vitro anti-proliferative properties, oleocanthal and oleacein, could slow the progression of chronic lymphatic leukemia [ 15 ].…”
mentioning
confidence: 99%